Conjugate-Based Targeting of Recombinant Adeno-Associated Virus Type 2 Vectors by Using Avidin-Linked Ligands - Ponnazhagan, Selvarangan (American Society for Microbiology (ASM), 2002)
The development of targeted vectors, capable of tissue-specific transduction, remains one of the important aspects of vector modification for gene therapy applications. Recombinant adeno-associated virus type 2 (rAAV-2)-based vectors are nonpathogenic, have relatively low immunogenicity, and are capable of long-term transgene expression. AAV-2 vectors bind primarily to heparan sulfate proteoglycan (HSPG), a receptor that is present in many tissues and cell types. Because of the widespread expression of HSPG on many tissues, targeted transduction in vivo appears to be limited with AAV-2 vectors. Thus, development of strategies to achieve transductional targeting will have a profound benefit in the future application of these vectors. We report here a novel conjugate-based targeting method to enhance tissue-specific transduction of AAV-2-based vectors. The present report utilized a high-affinity biotin-avidin interaction as a molecular bridge to cross-link purified targeting ligands, produced genetically as fusion proteins to core-streptavidin, in a prokaryotic expression system. Conjugation of the bispecific targeting protein to the vector was achieved by biotinylating purified rAAV-2 without abolishing the capsid structure, internalization, and subsequent transgene expression. The tropism-modified vectors, targeted via epidermal growth factor receptor (EGFR) or fibroblast growth factor 1α receptor (FGFR1α), resulted in a significant increase in transduction efficiency of EGFR-positive SKOV3.ip1 cells and FGFR1α-positive M07e cells, respectively. Further optimization of this method of targeting should enhance the potential of AAV-2 vectors in ex vivo and in vivo gene therapy and may form the basis for developing targeting methods for other AAV serotype capsids.